The benefits of flushing for mitigating Legionella spp. in non-chlorinated building plumbing systems - Meegoda, Charuka S.; Waak, Michael B.; Hozalski, Raymond M.; Kim, Taegyu; Hallé, Cynthia (Frontiers in Water, 2023)
Flushing is a common corrective action recommended by Legionella management guidelines to remove stagnant water and replenish disinfectant. Due to water age and different local regulations, buildings may receive water with low or no residual disinfectant. In such situations, the evidence for flushing efficacy is often anecdotal, and the benefits are poorly quantified. Using a pilot-scale premise plumbing system, flushed shower outlets were evaluated against non-flushed outlets during simulated periods of both active and low water demand. Water and biofilm concentrations of total bacteria, Legionella spp., and Vermamoeba vermiformis were quantified using real- time quantitative PCR. Even after all outlets returned to active water demand, flushed shower outlets continued to have lower quantities of Legionella compared to non-flushed outlets for several days, but the decrease was of little practical benefit (<0.5 log10[copies/L]). During prolonged periods of low water demand, however, there was no apparent benefit to flushing. Total bacteria grew to stationary phase within 3 ± 1 days, while Legionella spp. took 12 ± 6 days, regardless of whether the pipes had recently been flushed or not. In biofilms, flushing had no effect on bacterial concentrations, but Legionella were more commonly present in the cold water pipes compared to hot water and more so PEX compared to copper. In summary, flushing with hot water appears to have little practical benefit for managing Legionella in non-chlorinated building plumbing systems. The cold water system, which is not typically managed with flushing, is nonetheless a source of Legionella spp. as well as V. vermiformis and perhaps a similar or greater source of these taxa than hot water.